Short Term Portfolio Investment and BI Rate: Do They Determine the Stabilization of Rupiah Exchange Rate in Indonesia? - Seftarita, Chenny; Fitriyani, Fitriyani; Rizki, Cut Zakia; Sapha, Diana; Jamal, Abd. (Journal of Economic Development, Environment and People, 2019)
This study aims to investigate the influence of short-term portfolio investments and BI interest rate on fluctuation of rupiah exchange rate in Indonesia. The data used is quarterly data from 2010 to 2016 collected from Indonesia Central Bank. Using the Autoregressive Distributed Lag (ARDL) method, the result showed that rupiah exchange rate was strongly influenced by shocks in the private debt securities, joint stock price index, and BI Rate, both in the long run and short run. Moreover, it is found that there was a short-run and long-run balance relationship between Short Term Portfolio Investments and BI rate against the rupiah exchange rate. Thus, it is recommended that in order to stabilize the exchange rate, it is necessary to maintain the stability of short-term portfolio investments.